If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3ln(2x + 5) = 6 Reorder the terms: 3ln(5 + 2x) = 6 (5 * 3ln + 2x * 3ln) = 6 (15ln + 6lnx) = 6 Solving 15ln + 6lnx = 6 Solving for variable 'l'. Move all terms containing l to the left, all other terms to the right. Reorder the terms: -6 + 15ln + 6lnx = 6 + -6 Combine like terms: 6 + -6 = 0 -6 + 15ln + 6lnx = 0 Factor out the Greatest Common Factor (GCF), '3'. 3(-2 + 5ln + 2lnx) = 0 Ignore the factor 3.Subproblem 1
Set the factor '(-2 + 5ln + 2lnx)' equal to zero and attempt to solve: Simplifying -2 + 5ln + 2lnx = 0 Solving -2 + 5ln + 2lnx = 0 Move all terms containing l to the left, all other terms to the right. Add '2' to each side of the equation. -2 + 5ln + 2 + 2lnx = 0 + 2 Reorder the terms: -2 + 2 + 5ln + 2lnx = 0 + 2 Combine like terms: -2 + 2 = 0 0 + 5ln + 2lnx = 0 + 2 5ln + 2lnx = 0 + 2 Combine like terms: 0 + 2 = 2 5ln + 2lnx = 2 The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined. The solution to this equation could not be determined.
| 8x-2=6x+12 | | 6x+6+2x=24 | | 36-(-4)= | | 7+x+7-17=11 | | 27=7+9+C | | -19+-2= | | 11x+12-3x=30 | | 27=7 | | bx+d=a | | 7x-2=90 | | q^2+2q-16=0 | | 5x-4=4-d | | -42+-12= | | 35=7+12+C | | 4+17x=56 | | 6x+10=90 | | 8+x=56 | | 9t-18t=-18 | | 3(-2r-2)=-2(3r+3) | | 10x-2=8x+6 | | 13+-13= | | cy+by-cz-bz= | | (-6)2*(-6)5= | | 144=4*8*4+2*4*W | | cy+by-cz-bz=0 | | 6v+5-v=-5 | | 7x-11y-6y+3x+10= | | (-6)2(-6)5= | | -2x+2(2x-5)=x+x+x+2 | | 2x+160250= | | (16-3*5)q+13=(2*9-16)q+(1-1) | | 8(4)=(-3)m+1 |